Farming the city. The resilience and decline of urban agriculture in European history. - (:unkn) unknown (StudienVerl., 2020)
Urban agriculture is a highly diversified and multi-layered phenomenon, and its roots are both very old and very recent. Throughout European history, it has appeared in different forms and guises. In some periods and regions, urban agriculture seems to have declined at an early stage, whereas in others urban economies and societies remained firmly based on more or less specialized and commercialized agrarian production until the recent past. At the beginning of the 21st century, in an urban world characterized by globalizing food markets, social polarization, but also increasing food insecurity, it is again rapidly gaining importance. Citizens practice urban agriculture in a combined effort to diversify their food supplies, shorten the food chain and strengthen community life. In order to understand the organization, the resilience and failure of urban agriculture in different contexts, this volume aims to develop a comparative and long-term approach, with a particular focus on the actors involved in urban agriculture, their income strategies, and the social and economic configurations in which they operate.
Keywords: Stadtgeschichte; Siedlungsgeschichte; Urbaner Raum; Stadtraum; Nahrungsmittelproduktion; Agrarproduktion; Landwirtschaft; Gemeinschaftsnutzung; Städtische Landwirtschaft